COMPARATIVE ECONOMIC ASSESSMENT BETWEEN SMR PLANTS AND LARGE PLANT IN COMPARISON WITH CPP TAKING INTO ACCOUNT ENVIRONMENTAL ASPECT - Nasrullah, Mochamad (Ketenagalistrikan dan Energi Terbarukan, 2013)
Construction of N uclear Power Plant (NPP) in a country is always a controversy. The size of capacity on Nuclear Power Plant becomes important whether to use large capacity or small capacity, as this will give an effect in the Levelized Unit Electricity Cost. The study will assess the LUEC and the Levelized Unit Product Cost of electricity and non-electricity, also present a comparative economic assessment between SMR and large PWR, and comparison with different energy resources taking into account the environmental aspect. The models used to calculate the economics of power plants are G4Econs, IAEA’s models in spreadsheet form released in 2008. The models will take into account the investment cost, fuel cost, operational and maintenance (O&M) cost. Using 10% discount rate, the result of economic assessment shows that generation cost of large unit does not always cheaper the smaller units. Pembangunan PLTN disetiap negara selalu terjadi suatu kontroversi. Ukuran kapasitas PLTN menjadi penting apakah menggunakan kapasitas besar atau kecil, hal ini akan berpengaruh dalam biaya pembangkitan listrik. Studi ini akan memperkirakan biaya pembangkitan listrik dan biaya sampingan dari pembangkit listrik dan non listrik. Selain itu juga menyajikan suatu perbandingan perkiraan ekonomi antara PLTN ukuran SMR dan PLTN ukuran besar yang akan dibandingkan dengan sumber energi yang berbeda (PLTU) yang mempertimbangkan aspek lingkungan. Model yang digunakan untuk menghitung keekonomian PLTN tersebut adalah G4Econs. Model ini dibuat IAEA dalam bentuk spreadsheet yang dipublikasikan tahun 2008. Model ini akan menghitung biaya investasi, biaya bahan bakar, biaya operasi dan perawatan. Dengan menggunakan discount rate 10% hasil perhitungan ekonomi menunjukkan biaya pembangkitan ukuran besar tidak selalu murah jika dibandingkan dengan ukuran kecil.